Effects of graded fiber level and caecectomy on metabolizable energy value and amino acid digestibility in geese - Jing YANG; Shuang-shuang ZHAI; Yong-chang WANG; Shen-shen WANG; Zhi-peng YANG; Lin YANG; Wen-ce WANG (Journal of Integrative Agriculture)
This study was carried out to evaluate the effects of graded levels of fiber from rice hull and the caecectomy on metabolizable energy (ME) and amino acid digestibility (AAD) in 42 Wuzong geese (21 intact and 21 caecectomized). The experiment was a 3×2 factorial randomized design with 3 fiber levels and 2 treatments of geese (caecectomized and intact). Each of the 3 diets was tube-fed (60 g) to 7 caecectomized and 7 intact adult Wuzong geese that had been fasted for 24 h. Excreta were collected for the next 48 h. The same geese were also fasted for estimation of endogenous losses of amino acids (AA) and energy after short period recovery. AA content and metabolizable energy value were determined in the excreta. In general, significant effects were found for fiber levels on apparent digestibility of Thr, Leu, Pro, Glu, Val, Ala and total AA (P<0.05). Apparent metabolizable energy (AME) and true metabolizable energy (TME) were both significantly influenced by increased fiber levels (P<0.01). Compared with caecectomized geese, markedly increases of AME and TME were found in intact geese (P<0.01 for AME and P<0.05 for TME), but no difference in the AAD were found between intact and caecectomized geese (P>0.05), except for Lys and Try (P<0.05). These observations suggested that dietary fiber level played an important role in digestibility of AAD and ME. Intact geese should be chosen for the nutrient evaluation of feedstuffs in practice, resulting from the significant difference between caecectomized and intact geese.